PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN DENGAN INTEGRITAS KARYAWAN SEBAGAI VARIABEL PEMODERASI - Dita, Made Ambara; Putra, I Wayan (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
The purpose of this study was to determine the effect of the application of the system of accounting information on the performance of employees, whether the employees' integrity moderate the effects of the application of accounting information system on employee performance. This research was conducted at the Rural Bank in Karangasem. Samples in this study of 52 respondents to the sampling technique used was purposive sampling. The data collection method used is the method of questionnaires and interviews. Data analysis technique used is the technique of multiple linear regression analysis. Based on the results of research by distributing questionnaires to 52 respondents, it can be concluded that the application of the accounting information system and significant positive effect on employee performance. Employee integrity and significant positive effect on employee performance and integrity of employees as moderating the application of accounting information system and the integrity of the employee, the employee can demonstrate integrity moderate
Keywords: Application of Accounting Information Systems, Employee Performance, Integrity Employee.